2018
DOI: 10.1186/s12943-018-0834-9
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-originated exosomal lncUEGC1 as a circulating biomarker for early-stage gastric cancer

Abstract: Conventional tumor markers for non-invasive diagnosis of gastric cancer (GC) exhibit insufficient sensitivity and specificity to facilitate detection of early gastric cancer (EGC). We aimed to identify EGC-specific exosomal lncRNA biomarkers that are highly sensitive and stable for the non-invasive diagnosis of EGC. Hence, in the present study, exosomes from the plasma of five healthy individuals and ten stage I GC patients and from culture media of four human primary stomach epithelial cells and four gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(132 citation statements)
references
References 16 publications
6
116
0
Order By: Relevance
“…The plasma exosomal Sox2ot expression is high in PDAC patients and correlated with TNM stage and overall survival 43 . LncUEGC1 is confirmed to be remarkably upregulated in plasma exosomes of early stage gastric cancer (EGC) patients and has better diagnostic accuracy to discriminate EGC patients from healthy individuals and those with premalignant chronic atrophic gastritis than carcinoembryonic antigen (CEA) 46 . We showed that UFC1 was highly expressed in exosomes from NSCLC cells and serum of NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma exosomal Sox2ot expression is high in PDAC patients and correlated with TNM stage and overall survival 43 . LncUEGC1 is confirmed to be remarkably upregulated in plasma exosomes of early stage gastric cancer (EGC) patients and has better diagnostic accuracy to discriminate EGC patients from healthy individuals and those with premalignant chronic atrophic gastritis than carcinoembryonic antigen (CEA) 46 . We showed that UFC1 was highly expressed in exosomes from NSCLC cells and serum of NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cancer-derived lncRNAs can be packaged into exosomes and transported in circulating blood, which makes exosomal lncRNAs as an ideal noninvasive diagnostic and prognostic biomarker for cancer detection [21]. From recent studies, Lin et al demonstrated that plasma exosomal lncRNA UEGC1 originating from gastric cancer cells was highly sensitive to the early stage of gastric cancer [22]. Moreover, Sedlarikova et al reported that serum exosomal lncRNA PRINS could act as a diagnostic biomarker in multiple myeloma [23].…”
Section: Ivyspringmentioning
confidence: 99%
“…Moreover, several studies have indicated that serum exosomal lncRNAs show increased expression in several human cancers, including colorectal cancer, hepatocellular carcinoma, and gastric cancer. [10][11][12][13] Emerging evidence indicates H19 is an oncogene. 14 The H19 gene encodes a 2.3-kb lncRNA, which is located on human chromosome 11p15.5 and exclusively expressed from the maternal allele.…”
Section: Introductionmentioning
confidence: 99%